Expression of Transforming Growth Factor Betas and Their Signaling Receptors in Stone‐containing Intrahepatic Bile Ducts and Cholangiocarcinoma - Lee, King‐Teh; Liu, Tsan‐Shium (World journal of surgery, 2003)
Transforming growth factor betas (TGF‐βs) are multifunctional polypeptides that either inhibit or stimulate cell proliferation. They mediate their functions through their signaling receptors. Clinically, hepatolithiasis has been regarded as a risk factor for cholangiocarcinoma. The aim of this study was to examine the expression of TGF‐βs and their receptors in stone‐containing intrahepatic bile ducts (IHD) and cholangiocarcinoma and try to predict whether hepatolithiasis has a predisposition to development of cholangiocarcinoma. Twenty‐eight surgically resected specimens of stone‐containing IHD and 15 specimens of cholangiocarcinoma were subjects for this study. Immunohistochemical analysis was done on three TGF‐βs and their signaling receptors to check their expression in non‐neoplastic and neoplastic bile ducts. No immunoreactivity of TGF‐β1 was found in any specimens. The overexpression of TGF‐β2 and TGF‐β3 was found in both hepatolithiasis (93%–100%) and cholangiocarcinoma (80%) at levels significantly higher than those of normal controls (10%–20%) (p < 0.001). The immunoreactivity of type I receptor (TβRI) and type II receptor (TβRII) also showed increased expression in stone‐containing IHD, whereas TβRII was absent in cholangiocarcinoma. We conclude that the overexpression of TGF‐β2 and TGF‐β3 and the absence of TβRII in cholangiocarcinoma could lead to enhanced tumor cell proliferation. At the same time, the overexpression of TGF‐βs and their receptors in stone‐containing IHD could suggest a close relationship between hepatolithiasis and cholangiocarcinoma.